ETIKA KEKUASAAN: REFLEKSI FILOSOFIS ATAS MORALITAS DALAM TINDAKAN POLITIK - Rahmad - Ramadhan (Universitas Islam Negeri Imam Bonjol Padang, 2025)
AbstrakPower is a fundamental reality in human political life, yet its relationship with ethics has always been a subject of debate. In modern political practice, especially in Indonesia, power is often exercised through pragmatic logic that neglects moral values and public responsibility. This study aims to philosophically reflect on the relationship between power and ethics in political action and to reaffirm its relevance to contemporary Indonesian politics. Employing a philosophical hermeneutic approach, this research analyzes both classical and modern works including those of Plato, Machiavelli, Kant, Arendt, and Foucault alongside a contextual reading of political power in Indonesia. The reflection reveals that power detached from ethics tends to produce a moral legitimacy crisis and political dehumanization. Conversely, ethics provides a normative compass for the exercise of power to ensure justice, humanity, and moral accountability. In the Indonesian context, the values of Pancasila serve as the foundation of political ethics, balancing political effectiveness with moral integrity. Thus, this study emphasizes the necessity of constructing a paradigm of ethical power grounded in virtue, rational participation, and ethical awareness as the philosophical basis of a dignified democratic politics.